Adrenocortical status in infants and children with sepsis and septic shock - Hanaa I. Rady; Yasmin S. Aly; Mona Hafez; Hafez M. Bazaraa (SpringerOpen, 2014)
Background: The benefit from corticosteroids remains controversial in sepsis and septic shock and the presence of adrenal insufficiency (AI) has been proposed to justify steroid use. Aim: To determine adrenal state and its relation with outcome in critical children admitted with sepsis to PICU of Cairo University, Children Hospital. Methods: Thirty cases with sepsis and septic shock were studied. Cortisol levels (CL) were estimated at baseline and after high-dose short ACTH stimulation in those patients and in 30 matched controls. Absolute AI was defined as basal CL < 7 μg/dl and peak CL < 18 μg/dl. Relative AI was diagnosed if cortisol increment after stimulation is <9 μg/dl. Results: Overall mortality of cases was 50%. The mean CL at baseline in cases was higher than that of controls (51.39 μg/dl vs. 12.83 μg/dl, p = 0.000). The mean CL 60 min after ACTH stimulation was higher than that of controls (73.38 μg/dl vs. 32.80 μg/dl, p = 0.000). The median of %rise in cases was lower than that of controls (45.3% vs. 151.7%). There was a positive correlation between basal and post-stimulation cortisol with number of system failure, inotropic support duration, mechanical ventilation days, and CO2 level in blood. There was a negative correlation between basal and post stimulation cortisol with blood pH and HCO3. Conclusion: RAI is common with severe sepsis/septic shock. It is associated with more inotropic support and has higher mortality. Studies are warranted to determine whether corticosteroid therapy has a survival benefit in children with RAI and catecholamine resistant septic shock.